2019
DOI: 10.1101/783027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell genomic characterization reveals the cellular reprogramming of the gastric tumor microenvironment

Abstract: Purpose The tumor microenvironment (TME) consists of a heterogenous cellular milieu that can influence cancer cell behavior. The characteristics of the cellular TME have a dramatic impact on treatments such as immunotherapy. These features can be revealed with single-cell RNA sequencing (scRNA-seq). We hypothesized that single cell gene expression studies of gastric cancer (GC) together with paired normal tissue and peripheral blood mononuclear cells (PBMCs) would identify critical elements of cellular dysregu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 52 publications
3
50
1
Order By: Relevance
“…Although macrophages divisions based on their polarization states could be into three types: un-activated macrophages (M0 macrophages), the classically activated type 1 (M1 macrophages), and the alternatively activated type 2 [20]. Recent research on the genetically engineered mouse model of PDACs, as well as human primary gastric cancer revealed no such classi cation of clusters in the single-cell level [14,21]. The in vitro programming of M0 macrophage to M1 is thought to enhance the cytotoxicity against tumor cells by pro-in ammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although macrophages divisions based on their polarization states could be into three types: un-activated macrophages (M0 macrophages), the classically activated type 1 (M1 macrophages), and the alternatively activated type 2 [20]. Recent research on the genetically engineered mouse model of PDACs, as well as human primary gastric cancer revealed no such classi cation of clusters in the single-cell level [14,21]. The in vitro programming of M0 macrophage to M1 is thought to enhance the cytotoxicity against tumor cells by pro-in ammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we evaluated the two distinct single-cell-based platforms, scRNA-seq and CyTOF, for single-cell level immune profiling using surgery-/biopsy-resected tumors and PBMC from gastric cancer patients. The number of previous studies focusing on gastric cancer biopsy in single-cell level is limited [31][32][33] . Our study revealed that the scRNA-seq analysis could cover a broader range of immune cells of TME in the endoscopically-resected small biopsy tumor samples, detecting even small subgroups of B cells or Treg cells in the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, if the biopsy samples could be collected before and after the drug treatment in the same patients, the single-cell analysis with these pre-/ post-treatment specimens should provide a great advantage for a deep understanding of the mechanisms of actions and/or biomarker development for cancer therapeutic drugs [41][42][43] . In fact, the single-cell analyses in the biopsy samples, including the scRNA-seq analysis in gastric cancer, have received a lot of attention in recent years, while the number of reports is extremely limited [31][32][33] . Although several technical challenges still need to be cleared for scRNA-seq of the biopsy-resected tumors, especially the cell isolation steps to miss certain cell populations by "bottle-neck effects" 33,44 , this research platform of scRNA-seq should have potential to open the doors to the new generation of cancer biology, overcoming a number of difficulties that currently-used conventional methodologies are facing.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, their results suggest the potential value of GPNMB blockade as a new immunotherapy against GC 23 . Using single‐cell gene expression analysis, Sathe et al 24 demonstrated that GC TME suffers from a series of cellular changes compared to matched stomach mucosa. They reported an increased number of Tregs, which contribute to an immunosuppressive microenvironment and identified transcriptional cell states unique to GC in dendritic cells and two subclasses of exhausted cytotoxic T lymphocytes.…”
Section: Immune Microenvironmentmentioning
confidence: 99%